Koli fishermen at Bhaucha Dhakka (Ferry Wharf) - Mumbai Archive Project Team (Jio Institute, 2024)
Koli fishermen are sorting the day’s catch at Bhaucha Dhakka jetty. Due to extensive land reclamations, Kolis had to shift their fishing activities further south of the Mazagon dockyards. For their use, the Bhaucha Dhakka jetty was constructed in 1979. The jetty handles ferry services and maritime operations related to the commercial fishing industry.